2009
DOI: 10.1002/elsc.200800084
|View full text |Cite
|
Sign up to set email alerts
|

Purification and characterization of lignin peroxidase from Loweporus lividus MTCC‐1178

Abstract: Lignin peroxidase from the culture filtrate of Loweporus lividus MTCC‐1178 has been purified to homogeneity using Amicon concentration and DEAE cellulose chromatography. The molecular weight of the purified lignin peroxidase using SDS‐PAGE analysis has been found to be 40 kDa. The Km values for veratryl alcohol and H2O2 for the purified enzyme were 58 and 83 μM, respectively. The calculated kcat value of the purified enzyme using veratryl alcohol as the substrate was 2.5 s−1. The pH and temperature optima of l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 16 publications
0
16
1
Order By: Relevance
“…Work by Yadav et al . indicated that white‐rot fungi contain laccase and lignin peroxidase enzymes that can decay lignin in woods. However, it was interesting to note that the increasing rate of weight loss for WPVC and WHDPE did not change proportionally with the increased loadings of wood flour.…”
Section: Resultsmentioning
confidence: 99%
“…Work by Yadav et al . indicated that white‐rot fungi contain laccase and lignin peroxidase enzymes that can decay lignin in woods. However, it was interesting to note that the increasing rate of weight loss for WPVC and WHDPE did not change proportionally with the increased loadings of wood flour.…”
Section: Resultsmentioning
confidence: 99%
“…LiP is a biotechnologically important enzyme having wide potential applications (I) in delignification of lignocellulosic materials (Harley et al 1988), which are seen as an alternative to the depleting oil reserves, (II) in the conversion of coal to low molecular mass fractions (Catcheside and Ralph 1999), which could be used as a feed stock for the production of commodity chemicals, (III) in biopulping and biobleaching (Eriksson and Kirk 1994) [4] in paper industries, (IV) in removal of recalcitrant organic pollutants (Bumpus et al 1985;Kwant and Chang 1998;Satwinder et al 1998;Levin et al 2004;Cenek et al 2004) and (V) in the enzymatic polymerization (Hiroshi and Shiro 1999) in polymer industries. LiP of Phanerocheate chyrosoporium has been extensively studied (Tien and Kirk 1988;Vyas et al 1994;Kang et al 1993) and LiP of Trametes versicolor (Vyas et al 1994), Pleurotus ostreatus (Kang et al 1993), P.ostroiformis (Satyahari et al 1994), Ganoderma lucidum (Perumal and Kalaichelvan 1996), Aspergillus terreus (Meera et al 2002), Fusarium oxysporum (Meera et al 2002), Pencillium citrinum (Meera et al 2002), Rizopus nigrican (Shanmugan and Yadav 1997), Pleurotus sajor-caju (Shanmugan and Yadav 1996), Abortiporus biennis (Patel et al 2007), Pestalotia bicolor (Patel et al 2007), Heterobasidium annosum (Patel et al 2007), Gloephyllum striatum (Patel et al 2007), Loweporus lividus (Patel et al 2007), Pycnoporus sanguineus MTCC-137 , Lenzitus seperia MTCC-1170 (Yadav et al 2009a), Loweporus lividus MTCC-1178 (Yadav et al 2009b), Hexagona tenuis MTCC-1119 (Yadav et al 2010), Gleophyllum striatum MTCC-1117 and Lenzitus betulina MTCC-1183 (Meera Yadav et al 2012) have been reported. The lignin peroxidase isozymes are similar in structure and f...…”
Section: Lignin Peroxidasementioning
confidence: 97%
“…Lignin peroxidase of Phanerocheate chyrosoporium has been extensively studied (Tien and Kirk 1988;Vyas et al 1994;Kang et al 1993) and LiP of Trametes versicolor (Vyas et al 1994) [12], Pleurotus ostreatus (Kang et al 1993), P.ostroiformis (Satyahari et al 1994), Ganoderma lucidum (Perumal and Kalaichelvan 1996), Aspergillus terreus (Meera et al 2002), Fusarium oxysporum (Meera et al 2002), Pencillium citrinum (Meera et al 2002), Rizopus nigrican (Shanmugan and Yadav 1997), Pleurotus sajor-caju (Shanmugan and Yadav 1996), Abortiporus biennis (Patel et al 2007), Pestalotia bicolor (Patel et al 2007), Heterobasidium annosum (Patel et al 2007), Gloephyllum striatum (Patel et al 2007), Loweporus lividus (Patel et al 2007), Pycnoporus sanguineus MTCC-137 , Lenzitus seperia MTCC-1170 (Yadav et al 2009a), Loweporus lividus MTCC-1178 (Yadav et al 2009b), Hexagona tenuis MTCC-1119 (Yadav et al 2010), Gleophyllum striatum MTCC-1117 , Lenzitus betulina MTCC-1183 (Yadav et al 2012) have been reported. Our research interest in lignin peroxidases has prompted us to screen this fungal strain for the secretion of lignin peroxidase.…”
Section: Lignin Peroxidasementioning
confidence: 97%